The given equation is a Lagrange's linear equation. The auxiliary equations are
"\\dfrac{dx}{x(y^{2}-z^{2})}=\\dfrac{dy}{y(z^{2}-x^{2})}=\\dfrac{dz}{z(x^{2}-y^{2})}" .
Using the multipliers, "x,y,z" each of the equation is equal to
"\\dfrac{xdx+ydy+zdz}{x^{2}(y^{2}-z^{2})+y^{2}(z^{2}-x^{2})+z^{2}(x^{2}-y^{2})}"
Therefore,
"xdx+ydy+zdz=0\\\\\n\n\\text{Integrating, we get}\\\\\n\n\\dfrac{x^{2}}{2}+\\dfrac{y^{2}}{2}+\\dfrac{z^{2}}{2}=c\\\\\nx^{2}+y^{2}+z^{2}=c_{1}~~~~~~~~~~~~(1)"
Now, using the multipliers, "\\dfrac{1}{x}, \\dfrac{1}{y}, \\dfrac{1}{z}" each of the equation is equal to
"\\dfrac{\\frac{1}{x}dx+\\frac{1}{y}dy+\\frac{1}{z}dz}{y^{2}-z^{2}+z^{2}-x^{2}+x^{2}-y^{2}}"
Therefore,
"\\frac{1}{x}dx+\\frac{1}{y}dy+\\frac{1}{z}dz=0\\\\\n\\text{Integrating, we get}\\\\\n\\log x+\\log y+\\log z = \\log c_{2}\\\\\n\\log (xyz)=\\log c_{2}\\\\\nxyz = c_{2}~~~~~~~~~~~~~~~~~~~~~~~~(2)"
The general solution is given by,
"\\phi(c_{1},c_{2})=0\\\\\n\\phi(x^{2}+y^{2}+z^{2},xyz)=0\\\\"
Comments
Leave a comment